Jordan Economic Monitor, Spring 2017 : The Green Economic Boost - World Bank (World Bank, Washington, DC, 2017)
The Jordan Economic Monitor provides an update on key economic developments and policies over the past six months. It presents findings from recent World Bank work on Jordan. It places them in a longer-term and global context, and assesses the implications of these developments and otherchanges in policy on the country’s outlook. Its coverage ranges from the macro-economy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and thecommunity of analysts and professionals engaged in Jordan.